KOTAK PENITIPAN ALAS KAKI DI MASJID BERBASIS OTP VIA SMS DENGAN OPERATOR KONTROL - Ramadhani, Adissa; Lugazhtiardi, Lugazhtiardi; Sulistyo, Eko; Mahmudin, Mahmudin (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
This research aims to design a safe, easy-to-use, and efficient footwear storage system in mosques by utilizing OTP (One Time Password) technology sent via SMS and controlled by an operator. The methods used include literature studies, hardware and software design based on an ESP32 microcontroller and a SIM800L GSM module, tool assembly, and comprehensive system testing. Tests were conducted to measure the speed of OTP delivery, code validation, automatic lock performance, and the effectiveness of user interaction via the LCD and keypad. The test results show that the system is able to send OTPs in an average of 4–6 seconds, verify codes accurately, control the lock, and provide notifications to operators responsively. This system has been proven to improve storage security and provide greater comfort for the congregation, and can be implemented effectively in medium to large-scale mosque environments.